MiR‐205 Regulates Basal Cell Identity and Stem Cell Regenerative Potential During Mammary Reconstitution. (31st October 2018) - Lu, Yang; Cao, Jin; Napoli, Marco; Xia, Zheng; Zhao, Na; Creighton, Chad J.; Li, Wei; Chen, Xi; Flores, Elsa R.; McManus, Michael T.; Rosen, Jeffrey M.
Abstract: Mammary gland development is fueled by stem cell self‐renewal and differentiation. External cues from the microenvironment coupled with internal cues such as post‐transcriptional regulation exerted by microRNAs regulate stem cell behavior and fate. Here, we have identified a miR‐205 regulatory network required for mammary gland ductal development and stem cell regeneration following transplantation into the cleared mammary fat pad. In the postnatal mammary gland, miR‐205 is predominantly expressed in the basal/stem cell enriched population. Conditional deletion of miR‐205 in mammary epithelial cells impairs stem cell self‐renewal and mammary regenerative potential in the in vitro mammosphere formation assay and in vivo mammary reconstitution. miR‐205 null transplants display significant changes in basal cells, basement membrane, and stroma. NKD1 and PTPA, which inhibit the Wnt signaling pathway, and AMOT, which causes YAP cytoplasmic retention and inactivation were identified as miR‐205 downstream mediators. These studies also confirmed that miR‐205 is a direct Δ Np63 target gene that is critical for the regulation of basal cell identity.Stem Cells 2018;36:1875–15 Abstract : Putative model depicting how miR‐205 depletion may affect mammary gland development and stem cell self‐renewal during mammary reconstitution. The schematic representation of miR‐205 regulatory network:(A): miR‐205 is regulated by p63 and inhibits gene targets including Amot, Nkd1, and Ppp2r4, the negative regulators of YAP and Wnt pathway to potentially promote stem cell self‐renewal.(B): In the case of miR‐205 deletion, AMOT, NKD1, and PTPA expression is no longer repressed, leading to inhibition of YAP and the Wnt pathway, which affects stem cell self‐renewal and mammary gland morphogenesis.